The Influence of Boycott Threats on Abnormal Returns and Trading Volume: Evidence from the Israel-Palestine Conflict - Fanny Avianuari; Nur Dhani Hendranastiti (Dinasti International Journal of Education Management And Social Science, 2025)
This study examines the impact of the October 7, 2023 escalation of the Israel-Palestine conflict on companies targeted by boycott threats due to their alleged ties to Israel. Using abnormal returns (AR) and trading volume activity (TVA) as key indicators of stock performance, the research analyzes changes across 5-day, 30-day, and 120-day event windows. An event study methodology is applied to assess shifts in these indicators before and after the boycott threat. The results show a significant difference in TVA in the 5-day and 30-day event windows, indicating notable changes in trading behavior following the boycott. However, significant differences in abnormal returns were observed only in the 5-day window, with no significant changes in the 30-day and 120-day windows. Similarly, no significant difference in TVA was found in the 120-day event window, suggesting that the effects of the boycott diminished over time. These findings suggest that while the boycott influenced trading volume in the short term, its impact on stock prices, as measured by abnormal returns, was brief and faded over time.